2018
DOI: 10.17240/aibuefd.2018..-362044
|View full text |Cite
|
Sign up to set email alerts
|

Ortaokul Öğrenci̇leri̇ni̇n Çokgen Problemleri̇ndeki̇ Matemati̇ksel Düşünme Süreçleri̇

Abstract: Bu araştırmanın amacı ortaokul sekizinci sınıf öğrencilerinin çokgen ile ilgili problemlerdeki matematiksel düşünme süreçlerini incelemektir. Araştırmada verilerin toplanması, çözümlenmesi ve yorumlanmasında nitel araştırma yöntemi benimsenmiştir. Toplam sekiz öğrenci ile gerçekleştirilen araştırmanın verileri klinik görüşme yöntemi kullanılarak toplanmıştır. Öğrencilere genellemeye ulaşmaları beklenen çokgenler ile ilgili problemler sunulmuş, elde edilen veriler tematik olarak analiz edilmiştir. Özelleştirme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
6
0
2
Order By: Relevance
“…However, it should be noted that the two processes are interactive, interpretive techniques whereby listeners use both prior knowledge and linguistic knowledge to understand messages. Furthermore, as Vandergrift (2004, as cited in Yildirim & Yildirim, 2016) argues, depending on the purpose of listening, the listener can use top-down or bottom-up more than the other.…”
Section: Theoretical and Methodological Considerationsmentioning
confidence: 99%
“…However, it should be noted that the two processes are interactive, interpretive techniques whereby listeners use both prior knowledge and linguistic knowledge to understand messages. Furthermore, as Vandergrift (2004, as cited in Yildirim & Yildirim, 2016) argues, depending on the purpose of listening, the listener can use top-down or bottom-up more than the other.…”
Section: Theoretical and Methodological Considerationsmentioning
confidence: 99%
“…Because mathematics education has a function beyond teaching numbers and operations, gaining calculation skills that are an indispensable part of daily life, and provides important support such as thinking, making connections between events, making predictions, reasoning and solving problems. This way of thinking is called mathematical thinking (Yildirim, 2017). Stacey (2006) indicated that mathematical thinking, which can be defined as a natural tool in solving real-life problems, is an important requirement for learning and teaching mathematics, and therefore it is one of the most important goals of mathematics education.…”
Section: Introductionmentioning
confidence: 99%
“…A student with strong listening skills can comprehend and interpret what they hear (Ismail et al, 2023, p. 146;Raju, 2018, p. 14). In the 1970s, the ability to listen became more critical and was included in language programs alongside speaking, reading, and writing (Walker, 2014, p. 167;Yildirim & Yildirim, 2016, p. 2095. In reality, however, many teachers still need to consider the choice of listening media so that this one language skill often receives minimal attention, even though teachers are the spearhead of success in learning activities (Sudjana, 2004, p. 2) directly trying to influence, nurture, and develop students' abilities to become intelligent, skilled and highly moral human beings (Hendrawijaya, 2022, p. 858).…”
Section: Introductionmentioning
confidence: 99%